Potent PPAR gamma Ligands from Swietenia macrophylla Are Capable of Stimulating Glucose Uptake in Muscle Cells - Lau, W.K.; Goh, B.H.; Kadir, H.A.; Shu-Chien, A.C.; Muhammad, T.S.T. (2015)
Numerous documented ethnopharmacological properties have been associated with Swietenia macrophylla (Meliaceae), with its seed extract reported to display anti-hypoglycemic activities in diabetic rats. In the present study, three compounds isolated from the seeds of S. macrophylla were tested on a modified ELISA binding assay and showed to possess PPAR ligand activity. They were corresponded to PPAR-mediated cellular response, stimulated adipocyte differentiation but produced lower amount of fat droplets compared to a conventional anti-diabetic agent, rosiglitazone. The up-regulation of adipocytes was followed by increased adipocyte-related gene expressions such as adiponectin, adipsin, and PPAR. The S. macrophylla compounds also promoted cellular glucose uptake via the translocation of GLUT4 glucose transporter.